The role of cognitive and socio-emotional skills in labor markets - Pablo Acosta; Noel Muller (IZA World of Labor, 2018)
Common proxies, such as years of education, have been shown to be ineffective at capturing cross-country differences in skills acquisition, as well as the role they play in the labor market. A large body of research shows that direct measures of skills, in particular cognitive and socio-emotional ones, provide more adequate estimations of individuals' differences in potential productive capacity than the quantity of education they receive. Evidence shows that cognitive skills in particular are quite relevant to explain wages, while socio-emotional skills are more associated with labor force and education participation decisions.
Keywords: J24; J31; I24; 330; returns to skills; cognitive skills; socio-emotional skills; personality traits; labor market outcomes